Ergonomic interventions based on stretching to relieve low back pain and work fatigue in nurses - Jacob Matheos Ratu; Doppy Roy Nendissa; Mariana Dinah Charlota Lerik; Elizabeth B. Sawo; Anderias Umbu Roga (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: Low back pain (LBP) and work fatigue are common among nurses due to prolonged activity and poor posture. Effective interventions are needed to address these issues. Objective: To evaluate the effect of stretching exercises on reducing LBP and work fatigue in inpatient nurses at Prof. Dr. W.Z. Yohannes Kupang Hospital.